Investigation of stress distributions in the resin rich region and failure behavior in glass fiber composites with microvascular channels under tensile loading. (15th May 2018) - Al-Shawk, Ahmed; Tanabi, Hamed; Sabuncuoglu, Baris
Abstract: Microvascular channels in fiber-reinforced composites offer various functional enhancements such as damage monitoring and self healing. As an adverse effect, presence of such channels can harm the mechanical behavior of composites. In the present study, 3D models are generated to investigate the stress concentrations in the resin-rich pocket and failure behavior considering different stacking configuration and vascule sizes. Similar results were obtained for [0/90]4s and [90/0]4s stacking configuration in spite of having different layer just above the channel and different resin pocket dimensions. The effect of changing the vascule diameter is mostly observed in UD 0 configuration. Utilizing elliptical channels results in reduced stress concentrations compared to the circular ones with the same diameter. While the staking configuration affect the failure in the resin rich zone, it does not affect the failure from the laminate region.